Comparison of dabrafenib and trametinib combination therapy with vemurafenib monotherapy on health-related quality of life in patients with unresectable or metastatic cutaneous BRAF Val600-mutation-positive melanoma (COMBI-v): results of a phase 3, open-label, randomised trial. Issue 13 (October 2015) - Grob, Jean Jacques; Amonkar, Mayur M; Karaszewska, Boguslawa; Schachter, Jacob; Dummer, Reinhard; Mackiewicz, Andrzej; Stroyakovskiy, Daniil; Drucis, Kamil; Grange, Florent; Chiarion-Sileni, Vanna; Rutkowski, Piotr; Lichinitser, Mikhail; et al.
Summary: Background: In the COMBI-v trial, patients with previously untreated BRAF Val600Glu or Val600Lys mutant unresectable or metastatic melanoma who were treated with the combination of dabrafenib and trametinib had significantly longer overall and progression-free survival than those treated with vemurafenib alone. Here, we present the effects of treatments on health-related quality of life (HRQoL), an exploratory endpoint in the COMBI-v study. Methods: COMBI-v was an open-label, randomised phase 3 study in which 704 patients with metastatic melanoma with a BRAF Val600 mutation were randomly assigned (1:1) by an interactive voice response system to receive either a combination of dabrafenib (150 mg twice-daily) and trametinib (2 mg once-daily) or vemurafenib monotherapy (960 mg twice-daily) orally as first-line therapy. The primary endpoint was overall survival. In this pre-specified exploratory analysis, we prospectively assessed HRQoL in the intention-to-treat population with the European Organisation for Research and Treatment of Cancer quality of life (EORTC QLQ-C30), EuroQoL-5D (EQ-5D), and Melanoma Subscale of the Functional Assessment of Cancer Therapy—Melanoma (FACT-M), completed at baseline, during study treatment, at disease progression, and after progression. We used a mixed-model, repeated measures ANCOVA to assess differences in mean scores between groups with baseline score as covariate; all p-values are descriptive. The COMBI-v trial is registered withClinicalTrials.gov, numberNCT01597908, and is ongoing for the primary endpoint, but is not recruiting patients. Findings: From June 4, 2012, to Oct 7, 2013, 1645 patients at 193 centres worldwide were screened for eligibility, and 704 patients were randomly assigned to dabrafenib plus trametinib (n=352) or vemurafenib (n=352). Questionnaire completion rates for both groups were high (>95% at baseline, >80% at follow-up assessments, and >70% at disease progression) with similar HRQoL and symptom scores reported at baseline in both treatment groups for all questionnaires. Differences in mean scores between treatment groups were significant and clinically meaningful in favour of the combination compared with vemurafenib monotherapy for most domains across all three questionnaires during study treatment and at disease progression, including EORTC QLQ-C30 global health (7·92, 7·62, 6·86, 7·47, 5·16, 7·56, and 7·57 at weeks 8, 16, 24, 32, 40, 48, and disease progression, respectively; p<0·001 for all assessments except p=0·005 at week 40), EORTC QLQ-C30 pain (–13·20, −8·05, −8·82, −12·69, −12·46, −11·41, and −10·57 at weeks 8, 16, 24, 32, 40, 48, and disease progression, respectively; all p<0·001), EQ-5D thermometer scores (7·96, 8·05, 6·83, 11·53, 7·41, 9·08, and 10·51 at weeks 8, 16, 24, 32, 40, 48, and disease progression, respectively; p<0·001 for all assessments except p=0·006 at week 32), and FACT-M Melanoma Subscale score (3·62, 2·93, 2·45, 3·39, 2·85, 3·00, and 3·68 at weeks 8, 16, 24, 32, 40, 48, and disease progression, respectively; all p<0·001). Interpretation: From the patient's perspective, which integrates not only survival advantage but also disease-associated and adverse-event-associated symptoms, treatment with the combination of a BRAF inhibitor plus a MEK inhibitor (dabrafenib plus trametinib) adds a clear benefit over monotherapy with the BRAF inhibitor vemurafenib and supports the combination therapy as standard of care in this population. Funding: GlaxoSmithKline.